Iterative Hybrid Precoder and Combiner Design for mmWave Multiuser MIMO Systems - Wang, Zihuan; Li, Ming; Tian, Xiaowen; Liu, Qian (IEEE communications letters, 2017)
This letter investigates analog/digital hybrid precoder and combiner design for millimeter wave (mmWave) multiuser multiple-input multiple-output (MU-MIMO) systems. We propose a novel iterative algorithm for the joint hybrid precoder and combiner design by exploiting the duality of the uplink and downlink MU-MIMO channels. For the initialization stage, the proposed algorithm selects the analog precoder-combiner pair based on the orthogonal matching pursuit (OMP) algorithm to enhance the channel gain, while mitigating the multiple access interference, and obtains the digital combiner via minimum mean square error criterion. Then, the proposed algorithm enhances the performance gradually at each iteration via joint design of the uplink and downlink precoders/combiners. Simulation results demonstrate the significant performance advantages of the proposed precoder and combiner design compared with existing hybrid beamforming algorithms.